IMPLICATION OF CASH WAQF IN THE SOCIETY - Nurrachmi, Rininta (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2012)
This paper discusses the concept and process of waqf. It attempts to elaborate the real implication of cash waqf in the society, and also define the issue and challenge arises in managing waqf fund.